REDUCING GENDER DISPARITIES IN EFL CLASSROOMS THROUGH GAMIFIED LEARNING: AN ACTION RESEARCH STUDY USING BAAMBOOZLE IN INDONESIAN ELEMENTARY EDUCATION - Bouchra Eddraoui; Didi Sukyadi; Ahmad Bukhori Muslim; Bachrudin Musthafa (University of Kuningan, 2026)
Gender disparities often affect participation rates in language classrooms, with male pupils dominating discussions and activities. Therefore, effective educational practices to increase female students’ engagement in English-speaking classrooms are pertinent. This paper investigates the impact of Baamboozle, the digital-based game, in enhancing grade four female students’ involvement and motivation in English-speaking classes at an elementary integrated school in Bandung, Indonesia. Over 12 weeks, seven female students participated in action research, with data collected through classroom observations and a focus group discussion (FGD). Interpreted through the lens of the Sociocultural and Feminist Theories, findings revealed that the interactive and the collaborative nature of the game significantly improved female students’ cooperation, verbal communication skills, and classroom engagement. This study highlights that integrating digital games like Baamboozle not only enhances English language learning but also serves as a powerful pedagogical approach in fostering gender equity within the classroom.